Evidence of mutant huntingtin and tau-related pathology within neuronal grafts in Huntington’s disease cases - Salem, Shireen; Kilgore, Mitchell D.; Anwer, Mehwish; Maxan, Alexander; Child, Dan; Bird, Thomas D.; Keene, C. Dirk; Cicchetti, Francesca; Latimer, Caitlin (Neurobiology of disease, 2024)
A number of post-mortem studies conducted in transplanted Huntington’s disease (HD) patients from various trials have reported the presence of pathological and misfolded proteins, in particular mutant huntingtin (mHtt) and phosphorylated tau neuropil threads, in the healthy grafted tissue. Here, we extended these observations with histological analysis of post-mortem tissue from three additional HD patients who had received similar striatal allografts from the fetal tissue transplantation trial conducted in Los Angeles in 1998. Immunohistochemical staining was performed using anti-mHtt antibodies, EM48 and MW7, as well as anti-hyperphosphorylated tau antibodies, AT8 and CP13. Immunofluorescence was used to assess the colocalization of EM48+ mHtt aggregates with the neuronal marker MAP2 and/or the extracellular matrix protein phosphacan in both the host and grafts. We confirmed the presence of mHtt aggregates within grafts of all three cases as well as tau neuropil threads in the grafts of two of the three transplanted HD patients. Phosphorylated tau was also variably expressed in the host cerebral cortex of all three subjects. While mHtt inclusions were present within neurons (immunofluorescence co-localization of MAP2 and EM48) as well as within the extracellular matrix of the host (immunofluorescence co-localization of phosphacan and EM48), their localization was limited to the extracellular matrix in the grafted tissue. This study corroborates previous findings that both mHtt and tau pathology can be found in the host and grafts of HD patients years post-grafting. •mHTT aggregates are present within grafts in HD patients years post-surgery.•Tau neuropil threads are also observable within the grafted tissue.•Results corroborate previously published findings of two additional trials.